Literacy of Sharia Banking Contracts: Increasing Sharia Contract Understanding of Islamic Bording Scool Students in Raudhatunnasyi’ in Banjarbaru - Sauqi, Muhammad; Muyasarah, Iin (Faculty of Economics and Islamic Business State Islamic University of Palangka Raya, 2023)
Article (PKM) is motivated by the existence of the Raudhatunnasyi’in Islamic Boarding School Foundation which aims to provide a concrete understanding of the concept of muamalah and its implementation in Islamic Financial Institutions (LKS) so that the students of the Raudhatunnasyi’in Islamic Boarding School Foundation can apply it in a growing economic world. This research approach uses a service learning approach, which is an approach that combines academic learning objectives, interpersonal skills and contribution to society. This SL approach is very useful for students to test their understanding of the concepts or theories that have been learned. The results of this PKM are, first, the students of the Raudhatunnasyi’in Islamic Boarding School Foundation understand more about the concept of muamalah and its implementation in Islamic Financial Institutions (LKS). Second, the students of the Raudhatunnasyi’in Islamic Boarding School Foundation can apply the concept of muamalah contracts in their daily lives.